2010
DOI: 10.1590/s1677-04202010000400001
|View full text |Cite
|
Sign up to set email alerts
|

Activation of phenylalanine ammonia lyase as a key component of the antioxidative system of salt-challenged maize leaves

Abstract: Differential antioxidative activities were assessed in the leaves of two maize inbreds (A-180 and A-619) under salt stress and the subsequent recovery period. Total antioxidation test revealed that in both inbreds, this ability was sharply increased during stress period, but was slowly reverted back to the normal level during recovery. The enzymatic antioxidative analysis showed differential patterns in the activities of catalase, peroxidase and polyphenol oxidase in both maize inbreeds. Comparative analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 39 publications
(38 reference statements)
0
24
0
3
Order By: Relevance
“…TAL is enzyme which catalyses conversion of L-tyrosine to p-coumaric acid, one of the phenolic precursors, while the product of PAL activity is trans-cinnamic acid, formed by deamination of L-phenylalanine (R€ osler et al, 1997;Boudet, 2007). Most of the researches, which investigate the effect of plant elicitation on polyphenol production, are focused on the role of PAL in the biosynthetic pathway (Kim et al, 2005(Kim et al, , 2006aGholizadeh & Kohnehrouz, 2010). However, Dogbo et al (2012) suggested that the cumulative effect of both enzymes (PAL and TAL) was beneficial for the synthesis of phenols.…”
Section: Discussionmentioning
confidence: 99%
“…TAL is enzyme which catalyses conversion of L-tyrosine to p-coumaric acid, one of the phenolic precursors, while the product of PAL activity is trans-cinnamic acid, formed by deamination of L-phenylalanine (R€ osler et al, 1997;Boudet, 2007). Most of the researches, which investigate the effect of plant elicitation on polyphenol production, are focused on the role of PAL in the biosynthetic pathway (Kim et al, 2005(Kim et al, , 2006aGholizadeh & Kohnehrouz, 2010). However, Dogbo et al (2012) suggested that the cumulative effect of both enzymes (PAL and TAL) was beneficial for the synthesis of phenols.…”
Section: Discussionmentioning
confidence: 99%
“…The maceration in H 2 O:MeOH (1:1, v:v) facilitated the preparation of extracts in which polyphenols are abundant. Polyphenols are molecules highly biosynthesized in plants in which exercise primarily a defensive role against the overproduction of reactive oxygen species induced by abiotic stresses (Gholizadeh and Kohnehrouz, 2010). The metabolites identified are reported in Fig.…”
Section: Esi Ms N Metabolic Profiling Of Extracts From T Longicaulismentioning
confidence: 99%
“…The activity of PAL was unchanged in the buffer and water interacted control leaves. The increased activity of PAL has been previously reported in response to various biotic and abiotic stresses in plant system (Liang et al, 1989;Dixon & Paiva 1995;Chen et al, 2009;Gholizadeh & Baghbankohnehrouz, 2010;Ziaeil et al, 2012). The elevations in PAL activity has been shown in both compatible and incompatible plant interactions with environmental cues.…”
Section: Changes In Enzyme Activitiesmentioning
confidence: 57%
“…1; compounds possibly including antioxidative phenolic/polyphenolics that are generally synthesized by phenylpropanoid pathway. PAL, PPO and POD are not only responsible enzymes in lignification apparatus in plants, but also they are known as the key components of the antioxidative system of various stress-challenged plants (Stepien & Klobus, 2005;Gholizadeh & BaghbanKohnehrouz, 2010). Our experiment data may restate this question that how much does antioxidative sterategy help to the protection process of protein fraction-interacted plant tissue.…”
Section: Changes In the Antioxidative Statusmentioning
confidence: 69%